Penerapan Pencatatan Akuntansi Persediaan Bantal Hamil Berdasarkan Pernyataan Standar Akuntansi Keuangan Nomor 14 Tentang Persediaan: Studi Kasus pada Toko Online Shop My Bunda Collection - Kiki Hardiansyah; Fauzi Arafat (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Inventory is one of the important elements in a manufacturing company, considering its significant value and role as one of the main sources of profit. Inventory can be defined as goods owned by a company to be sold in the course of normal business activities or as raw materials used and consumed in the production process to produce goods to be marketed. This study aims to analyze the application of accounting records for maternity pillow inventory based on Financial Accounting Standards Statement (PSAK) No. 14 concerning inventory, with a case study at the My Bunda Collection Online Shop. The approach used in this study is a qualitative approach with a descriptive design. Data were collected through observation, structured interviews, and documentation. Data analysis was carried out using the adjustment description method, namely informal observation where researchers have determined behavioral indicators to be observed in the research subjects. The results of the study indicate that the inventory accounting recording system at the My Bunda Collection Online Shop uses a computer-based perpetual system. In addition, the inventory valuation method applied is FIFO (First In, First Out). The application of inventory accounting records at My Bunda Collection is in accordance with the standards set out in PSAK No. 14.